2016
DOI: 10.3389/fmicb.2016.01308
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Streptococcus agalactiae Causing Community- and Hospital-Acquired Infections in Shanghai, China

Abstract: Streptococcus agalactiae, a colonizing agent in pregnant women and the main cause of neonatal sepsis and meningitis, has been increasingly associated with invasive disease in nonpregnant adults. We collected a total of 87 non-repetitive S. agalactiae isolates causing community-acquired (CA) and hospital-acquired (HA) infections in nonpregnant adults from a teaching hospital in Shanghai between 2009 and 2013. We identified and characterized their antibiotic resistance, sequence type (ST), serotype, virulence, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 42 publications
(76 reference statements)
7
33
2
Order By: Relevance
“…25,26 Early-and late-onset disease is particularly attributed to serotypes III (mainly represented by ST19 in Asia and ST17 in Europe) and Ia (mainly represented by ST23 and ST24). 12,27 We found that serotype II isolates (represented by ST1, belonging to CC1) colonized neonates readily and in some cases they persisted in neonates up to 6 months; however, serotype II GBS causing late-onset and very-late-onset disease rarely occurred. 27,28 Another common serotype colonizing neonates was serotype III, as described above, and was the most common serotype to cause late-onset disease in neonates.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…25,26 Early-and late-onset disease is particularly attributed to serotypes III (mainly represented by ST19 in Asia and ST17 in Europe) and Ia (mainly represented by ST23 and ST24). 12,27 We found that serotype II isolates (represented by ST1, belonging to CC1) colonized neonates readily and in some cases they persisted in neonates up to 6 months; however, serotype II GBS causing late-onset and very-late-onset disease rarely occurred. 27,28 Another common serotype colonizing neonates was serotype III, as described above, and was the most common serotype to cause late-onset disease in neonates.…”
Section: Discussionmentioning
confidence: 89%
“…Although the maternal carriage rate in Taiwan is close to that in the entire AsiaePacific region (i.e., 19%), this rate actually varies among regions and countries, such as 8.0% in Korea, 8.2% in Japan, 7.1% in Beijing, China, and 7.1% in Hong Kong. 17e23 Among the 10 serotypes of GBS, the five most common are Ia, Ib, II, III, and V, 12,13,24 accounting for 96 and 88% of invasive GBS isolates from neonates and adults, respectively. 25,26 Early-and late-onset disease is particularly attributed to serotypes III (mainly represented by ST19 in Asia and ST17 in Europe) and Ia (mainly represented by ST23 and ST24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martins et al (12) also showed that ST19 comprised a GBS serotype III that was associated with colonising infection. In addition, a study conducted in China reported the prevalence of ST19 among serotype III isolates that caused community-and hospital-acquired infections (13).…”
Section: Discussionmentioning
confidence: 99%
“…Group B Streptococcus strains are divided into 10 distinct serotypes (Ia, Ib and II–IX), based on their polysaccharide component (Chang et al, ). Among them, capsular serotypes Ⅲ, Ia, Ib and Ⅴ are the most common in humans in China (Jiang et al, ; Wang et al, ). However, in the past decade, GBS strains of the Ia, Ib and III serotypes were shown to predominate in fish infections, and serotype Ia and Ib strains are mainly responsible for tilapia streptococcosis (Barato, Martins, Melo‐Cristino, Iregui, & Ramirez, ; Barony et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%